PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 1 BASO - Siddiq, Farhan (Jurnal Edukasi dan Penelitian Matematika, 2025)
One of the skills that students must master is the ability to communicate mathematical ideas.  Class IX at SMP Negeri 1 Baso is still at a minimum skill in this regard.  The implementation of the Think Talk Write (TTW) cooperative model is expected to overcome these problems.  This research used a non-equivalent posttest-only control group.  The results of the test, when analyzed by t-test, revealed a P-value = 0.019 at a significance level of α = 0.05.  Based on the performance on the test given using the TTW model, it can be concluded that the model is better in promoting mathematical communication skills when compared to direct learning.Keywords– Direct Learning, Mathematical communication skills, Think Talk Write